A case report of effective intra-articular elcatonin administration in a patient with osteonecrosis of the lunate. (April 2023) - Nagai, Takashi; Tomita, Kazunari; Kubo, Kazutoshi; Ikeda, Jun; Kawasaki, Keikichi; Inagaki, Katsunori
Abstract: Introduction and importance: Although corticosteroids are effective for bronchial asthma, they are associated with various side effects, such as osteonecrosis of the femoral head and tibial condyle and osteoporosis. Here, we report a patient who was on corticosteroids for a long period of time due to severe asthma, which was thought to have led to lunate osteonecrosis of both wrist joints. Calcitonin (elcatonin), an osteoporosis drug, was administered to the wrist joint. Case presentation: Allergy to anesthetics and various non-steroidal anti-inflammatory drugs (NSAIDs) made surgical treatment not possible and pain control difficult. In addition, pain in the wrist joint interfered with activities of daily living (ADLs). When calcitonin was administered intra-articularly into the wrist joint, the pain in the wrist joint was relieved and ADLs were improved. However, the pain-suppressing effect lasted only 1 week, and pain returned to the original state by the second week after treatment. Repeated injections were necessary every 2 weeks. Clinical discussion: This is the first report of the effectiveness of intra-articular calcitonin in a patient with osteonecrosis of the lunate. This treatment may be applicable to patients with allergies to anesthesia and NSAIDs. Conclusion: In the present case, calcitonin administered intra-articularly to the wrist appeared to be effective in pain control for steroid-induced lunate osteonecrosis. Highlights: Pain improved with intra-articular administration of elcatonin. Even in cases where NSAIDs are not available, elcatonin is effective in pain control. Administration of elcatonin increases blood flow and skin temperature.